Exploring Nanoscale Perovskite Materials for Next-Generation Photodetectors: A Comprehensive Review and Future Directions - Li, Xin; Aftab, Sikandar; Mukhtar, Maria; Kabir, Fahmid; Khan, Muhammad Farooq; Hegazy, Hosameldin Helmy; Akman, Erdi (Nano-Micro Letters, 2024)
The rapid advancement of nanotechnology has sparked much interest in applying nanoscale perovskite materials for photodetection applications. These materials are promising candidates for next-generation photodetectors (PDs) due to their unique optoelectronic properties and flexible synthesis routes. This review explores the approaches used in the development and use of optoelectronic devices made of different nanoscale perovskite architectures, including quantum dots, nanosheets, nanorods, nanowires, and nanocrystals. Through a thorough analysis of recent literature, the review also addresses common issues like the mechanisms underlying the degradation of perovskite PDs and offers perspectives on potential solutions to improve stability and scalability that impede widespread implementation. In addition, it highlights that photodetection encompasses the detection of light fields in dimensions other than light intensity and suggests potential avenues for future research to overcome these obstacles and fully realize the potential of nanoscale perovskite materials in state-of-the-art photodetection systems. This review provides a comprehensive overview of nanoscale perovskite PDs and guides future research efforts towards improved performance and wider applicability, making it a valuable resource for researchers. Highlights: 1 Innovative synthesis method for nanoscale-based perovskites with enhanced stability and efficiency. 2 Novel application of nanoscale-based perovskites in optoelectronics with superior performance metrics. 3 Comprehensive analysis of the structure–property relationships in perovskite nanomaterials.